Novel Chloroimidazolium‐Based Ionic Liquids: Synthesis, Characterisation and Behaviour as Solvents to Control Reaction Outcome. Issue 6 (27th May 2016) - Hawker, Rebecca R.; Panchompoo, Janjira; Aldous, Leigh; Harper, Jason B.
Abstract: Novel ionic liquids containing chlorine atoms on the imidazolium cation were synthesised. The physicochemical properties of these ionic liquids were investigated extensively, including glass transition, melting and decomposition temperatures, density, viscosity, miscibility with common solvents and electrochemical window. The behaviour of these ionic liquids as solvents was examined through temperature‐dependent kinetic analyses on two reactions: a nucleophilic aromatic substitution (SN Ar) reaction and a bimolecular nucleophilic substitution (SN 2) reaction. The properties and effects on reaction outcome of these new ionic liquids were shown to correlate with the change in the nature of the cation. Abstract : Rational design : A series of novel chloroimidazolium derivatives is described. Thermal and physical properties, electrochemical behaviour and solvent effects all fit the developing predictive framework for ionic liquids (see figure).